2017
DOI: 10.1128/mbio.02238-16
|View full text |Cite
|
Sign up to set email alerts
|

A Localized Complex of Two Protein Oligomers Controls the Orientation of Cell Polarity

Abstract: Signaling hubs at bacterial cell poles establish cell polarity in the absence of membrane-bound compartments. In the asymmetrically dividing bacterium Caulobacter crescentus, cell polarity stems from the cell cycle-regulated localization and turnover of signaling protein complexes in these hubs, and yet the mechanisms that establish the identity of the two cell poles have not been established. Here, we recapitulate the tripartite assembly of a cell fate signaling complex that forms during the G1-S transition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 50 publications
7
72
2
Order By: Relevance
“…S4). Despite previous reports of inactivity [18] and our own data predicting inactivation of its catalytic cleft due to its D20L mutation, we found that purified SpmX muramidase exhibited hydrolytic activity. We used remazol brilliant blue (RBB) assays, which are standard for measuring lysozyme activity [33], to compare the activity of SpmX muramidase from C. crescentus (SpmX-Mur-Cc) to that of the P22 lysozyme (P22Lyso) and a P22Lyso mutant with a similarly inactivated catalytic cleft (P22Lyso-D20L) ( Fig.…”
Section: Spmx Retains Reduced Hydrolytic Activity On Peptidoglycancontrasting
confidence: 99%
See 4 more Smart Citations
“…S4). Despite previous reports of inactivity [18] and our own data predicting inactivation of its catalytic cleft due to its D20L mutation, we found that purified SpmX muramidase exhibited hydrolytic activity. We used remazol brilliant blue (RBB) assays, which are standard for measuring lysozyme activity [33], to compare the activity of SpmX muramidase from C. crescentus (SpmX-Mur-Cc) to that of the P22 lysozyme (P22Lyso) and a P22Lyso mutant with a similarly inactivated catalytic cleft (P22Lyso-D20L) ( Fig.…”
Section: Spmx Retains Reduced Hydrolytic Activity On Peptidoglycancontrasting
confidence: 99%
“…Previously, it was suggested that the muramidase domain was co-opted entirely for the purpose of protein-protein and self-oligomerizing interactions in SpmX's role as a developmental regulator and scaffold in C. crescentus [18]. This conclusion was based on the lack of detectable activity from the purified domain and the inability of the catalytic E11R (E19R in SpmX numbering) mutant to self-oligomerize.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations